Predictive model for the therapeutic effect of bilateral subthalamic nucleus deep brain stimulation on the freezing of gait in Parkinson’s disease - Limuge, Qi; Zhang, Yuqing; Jia, Xiaofei; Wang, Fang; Yu, Dongsheng; Chen, Lixia; Zhang, Li; Jiang, Yongqiang (Frontiers in Aging Neuroscience, 2025)
BackgroundFreezing of gait (FOG) is a major disabling symptom that affects the quality of life of patients with Parkinson’s disease (PD). To date, notions regarding the effects of deep brain stimulation of the subthalamic neucleus (STN-DBS) on FOG remain controversial. Therefore, we developed a prediction model based on the influence of bilateral deep brain stimulation (DBS) of the subthalamic nucleus (STN) on FOG in patients with PD.MethodsWe collected data from 104 PD participants with FOG who underwent STN-DBS at Xuanwu Hospital between September 2017 and June 2022. The patients were divided into a training set (70%; n = 68) and a validation set (30%; n = 36). The selected characteristics in the LASSO regression were used in multivariate logistic regression to build the prediction model. The receiver operating characteristic (ROC) curves were constructed for the training and validation sets to verify the model’s efficiency.ResultsIndependent variables in the prediction model included Unified Parkinson’s Disease Rating Scale II (UPDRS II), UPDRS IV, leg rigidity, Montreal Cognitive Assessment (MoCA) score, and Mini-Mental State Examination (MMSE) score. The prediction model formula is as follows: Logit(y) = −1.0043 + 0.159 × UPDRS II + 0.030 × UPDRS IV - 1.726 × leg rigidity + 0.121 × MoCA + 0.036 × MMSE. To validate the model, we analyzed the ROC curves of the training and validation sets. The area under the ROC curve (AUC) of internal validation was 0.869 (95% confidence interval [CI]: 0.771–0.967) and the AUC of external validation was 0.845 (95% CI: 0.6526–1). The calibration plots showed good calibration.ConclusionThe model we developed can effectively assist clinicians in assessing the efficacy of deep brain stimulation of the bilateral subthalamic nucleus for freezing of gait in Parkinson’s disease patients. This approach can support the formulation of personalized treatment plans and has the potential to improve patient outcomes.